The Provence cure for the brokenhearted [compact disc, unabridged] : a novel - Asher, Bridget (Blackstone Audio, 2011)
Brokenhearted, still mourning the loss of her husband, Heidi travels with her son Abbott and her niece Charlotte to spend the summer repairing their family home in a small village in the south of France. There, thousands of miles from home, Charlotte makes a shocking confession, and Heidi learns the truth about her mother's "lost summer."